2004
DOI: 10.1002/jcb.20135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phenylephrine‐induced cardiac hypertrophy by docosahexaenoic acid

Abstract: Many of the cardiovascular benefits of fish oil result from the antiarrhythmic actions of the n-3 polyunsaturated lipids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). The beneficial effects of DHA/EPA in patients with coronary artery disease and myocardial infarction may also result from modulation of the myocardial hypertrophic response. Hypertrophy was assessed in neonatal cardiomyocytes exposed to phenylephrine (PE) by measuring cell surface area, total protein synthesis ((14)C leucine incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 88 publications
(90 reference statements)
0
30
0
Order By: Relevance
“…Cell hypertrophy was induced by phenylephrine (PE, Sigma-Aldrich) at a final concentration of 100 μM for 48 h in serum-free media, following a procedure published previously [9]. At the end of the 48 h incubation, Cu in the form of copper sulfate was added directly to the cultures at a final concentration of 5 μM Cu element for additional 24 h incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Cell hypertrophy was induced by phenylephrine (PE, Sigma-Aldrich) at a final concentration of 100 μM for 48 h in serum-free media, following a procedure published previously [9]. At the end of the 48 h incubation, Cu in the form of copper sulfate was added directly to the cultures at a final concentration of 5 μM Cu element for additional 24 h incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary fish oils can prevent LVH in transgenic mice with a carnitine transporter mutation, which was attributed to modified diacylglycerol composition and resultant inhibition of PKC activation [190]. Siddiqui et al demonstrated that n-3 polyunsaturated lipid docosahexaenoic acid (DHA) prevents cardiac hypertrophy by inhibition of the Ras-Raf1-Erk1/2-p90 rsk signaling pathway in a phenylephrine-induced hypertrophy model [191]. The role of PUFAs on lipid signaling via the PPAR system in cardiomyocytes remains to be clarified.…”
Section: Polyunsaturated Fats and Fish Oilsmentioning
confidence: 97%
“…Takahashi et al (45) observed that dietary FO prevented the membrane translocation of several cytosolic protein kinase C isozymes and suggested that this may be the mechanism for the hypertrophy suppression in the JVS mice. In vitro studies in isolated neonatal rat cardiac myocytes (sex of rats not reported) have demonstrated that DHA and EPA inhibit the growth response (i.e., protein synthesis) induced by phenylephrine and endothelin-1 stimulation via the Ras/Raf/Erk1/2 and JNK signaling pathways (41,42). In the present study, the growth reduction effect of FO diet was observed without a prior hemodynamic loading stimulus and therefore likely reflects a direct modulation of intrinsic myocardial trophic maintenance signaling.…”
Section: Discussionmentioning
confidence: 99%